2021
DOI: 10.3390/diagnostics11020290
|View full text |Cite
|
Sign up to set email alerts
|

Role of Albuminuria in Detecting Cardio-Renal Risk and Outcome in Diabetic Subjects

Abstract: The clinical significance of albuminuria in diabetic subjects and the impact of its reduction on the main cardiorenal outcomes by different drug classes are among the most interesting research focuses of recent years. Although nephrologists and cardiologists have been paying attention to the study of proteinuria for years, currently among diabetics, increased urine albumin excretion ascertains the highest cardio-renal risk. In fact, diabetes is a condition by itself associated with a high-risk of both micro/ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 121 publications
0
20
0
Order By: Relevance
“…Albuminuria and tubular atrophy are also risk factors for the progression of CKD to ESRD, and kidney proximal tubule lipoapoptosis is caused by dysregulation of fatty acid transporter-2 (FATP2), which may be an appropriate molecular target for the treatment of CKD [ 43 ]. Proteinuria represents a significant prognostic factor for onset and progression of DKD and CVD, reducing proteinuria can improve the cardio-renal outcomes in diabetic patients [ 44 ]. On the other hand, CKD is one of the strongest risk factors for the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Albuminuria and tubular atrophy are also risk factors for the progression of CKD to ESRD, and kidney proximal tubule lipoapoptosis is caused by dysregulation of fatty acid transporter-2 (FATP2), which may be an appropriate molecular target for the treatment of CKD [ 43 ]. Proteinuria represents a significant prognostic factor for onset and progression of DKD and CVD, reducing proteinuria can improve the cardio-renal outcomes in diabetic patients [ 44 ]. On the other hand, CKD is one of the strongest risk factors for the development of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Reduction of Endpoints in NIDDM with the Angiotensin II Antagonist Losartan (RENAAL) study showed that reduction in albuminuria by 50% was associated with reduced risks of cardiovascular events by 18% and heart failure by 27%. 24 People with T2D and moderately to severely increased albuminuria have an approximately threefold, fourfold, and fivefold greater risk of myocardial infarction, cardiovascular death and hospitalization for heart failure, respectively, than those with T2D alone. 25 A recent study (n=512 700) showed that early CKD in people with diabetes may shorten life expectancy by 16 years, compared with 6 years for early CKD without diabetes (either type 1 or type 2), and 10 years for diabetes alone (either type 1 or type 2; figure 2 ).…”
Section: Albuminuria As a Marker Of Kidney Damage And Cardiorenal Riskmentioning
confidence: 98%
“…While elevated albuminuria can be indicative of CKD, incremental increases in albuminuria are associated with corresponding increases in cardiorenal risk. 24 Concomitant CKD and T2D is an independent risk factor for cardiovascular events, with this population being approximately three times more likely to die from cardiovascular-related causes than those with T2D alone, and almost six times more likely to die from cardiovascular-related causes than those with neither T2D nor CKD. 5 Based on a report from the Framingham Heart Study, the presence of albuminuria is associated with a higher risk of incident heart failure, specifically heart failure with reduced ejection fraction, in the general population.…”
Section: Albuminuria As a Marker Of Kidney Damage And Cardiorenal Riskmentioning
confidence: 98%
“…One of the risk factors for kidney damage is oxidative stress. 24 One of the markers of oxidative stress found to be increased in patients with CKD is a product of nucleic acid oxidation, which is 8-OHdG. 25 8-OHdG or 8-oxo-7,8-dihydro-2'deoxyguanosine (8-oxodG) are free radicals commonly found due to oxidative injury and often become markers of oxidative stress or carcinogenesis.…”
Section: -Ohdg and Chronic Kidney Diseasementioning
confidence: 99%